2010
DOI: 10.1007/s11134-010-9180-3
|View full text |Cite
|
Sign up to set email alerts
|

Regularly varying tail of the waiting time distribution in M/G/1 retrial queue

Abstract: We consider an M/G/1 retrial queue where the service time distribution has a regularly varying tail with index −β, β > 1. The waiting time distribution is shown to have a regularly varying tail with index 1 − β, and the pre-factor is determined explicitly. The result is obtained by comparing the waiting time in the M/G/1 retrial queue with the waiting time in the ordinary M/G/1 queue with random order service policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Multiplying (8) by z − 1, letting z tend to 1, and using (11) and (12), we have assertion (9). In a similar manner, we can obtain (10).…”
Section: Lemmamentioning
confidence: 74%
See 2 more Smart Citations
“…Multiplying (8) by z − 1, letting z tend to 1, and using (11) and (12), we have assertion (9). In a similar manner, we can obtain (10).…”
Section: Lemmamentioning
confidence: 74%
“…Kim et al [10] showed that the tail of the queue size distribution is asymptotically given by a geometric function multiplied by a power function. On the other hand, Shang et al [16] and Kim and Kim [9] studied heavy-tailed asymptotics in the M/G/1 retrial queue. Shang et al [16] showed that the stationary distribution of the queue size in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue size in the corresponding ordinary M/G/1 queue is subexponential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kim et al [13] generalized the results in [10] to the MAP/G/1 retrial queue. Shang et al [16] and Kim and Kim [11] studied heavy-tailed asymptotics in the M/G/1 retrial queue. Shang et al [16] showed that the stationary distribution of the queue size in the M/G/1 retrial queue is subexponential if the stationary distribution of the queue size in the corresponding ordinary M/G/1 queue is subexponential.…”
Section: Introductionmentioning
confidence: 99%
“…Heath et al, 1998;Mikosch et al, 2002),queueing theory (cf. Cohen, 1973;Frenk, 1982;Kim et al, 2010;Olvera-Cravioto et al, 2010) and approximation of the ruin probabilities (cf. Gaier and Grandits, 2002;Klüppelberg and Stadtmüller, 1998).…”
Section: Heavy-tailed Distributionsmentioning
confidence: 99%